Evaluación del efecto de la aplicación de gonadotropina coriónica equina (ecg), en protocolos de sincronización en vacas holstein friesian mestizas en la hoya de Loja - Acaro Vargas, Guicela Maribel (2021)
Currently there are many limitations for the application of reproductive biotechnologies such as artificial insemination in dairy cattle under grazing conditions, among the most important are the failures in the detection of heat, postpartum anestrus, anes- trus due to food restriction, etc. The objective of this research was to evaluate the effect of the application of equine chorionic gonadotropin (eCG) in synchronization protocols in crossbred Holstein Friesian cows in the Loja basin. 24 bovine females with low body condition, aged between 3 and 6 years, were used in a postpartum period between 45 to 120 days with an average between 2 to 4 calvings. The cows were divided into three treatments: T1: (day 0: BE (Estradiol benzoate) + DIB (pro- gesterone releasing intravaginal device); day 6: 500 IU of eCG (Equine chorionic gonadotropin); day 8: removal of DIB + PGF2 α (prostaglandin); day 9: BE; Day 10 artificial insemination (IA); day 40: gestation determination); T2: (Day 0: BE + DIB; day 7: 500 IU of eCG; day 8: removal of DIB + PGF2 α; day9: BE; Day 10 IA; Day 40: determination of pregnancy); T3: (day 0: BE + DIB. day 8: removal of DIB + PGF2 α + 500 IU of eCG; day 9: BE; day 10: IA; day 40: pregnancy determination). The data reflected in the diameter of the dominant follicle, the largest was T3 with an average of 16 ± 1.41 mm, followed by T2 with 15 ± 1.85 mm and T1 with 11.1 ± 7.18 mm; in the pre-ovulatory follicle, T3 treatment obtained 18.8 ± 1.16 mm, followed by T2 with 17.9 ± 2.42 mm, and T1 13.3 ± 13.3 mm; the pregnancy percentage obtained T3 with 63 %, followed by T2 with 50 % and T1 with 38 %.In conclusion, the application of eCG applied on day 8 improved a diameter of the dominant follicle, diameter of the preovulatory follicle and the percentage of gestation. Key words: eCG; Postpartum anestrus; Body condition.